Análisis diseño e implementación de un entorno virtual de aprendizaje como apoyo a la asignatura de matemáticas, dirigido a los estudiantes de noveno de educación general básica de la unidad educativa “Amelia Gallegos Díaz”, 2016 - Pérez Gunsha, Jésica Maribel (2016)
In the digital version of the text of the website of the Department of Education, not technological resources such as virtual classrooms, educational software, multimedia guides, which serve as support for mathematics, were found. Innovation in this area is important for the level of complexity representing mathematical exercises. EVA creation was essential because it allowed students to use as a tool to support their learning. Therefore this research aims to create a virtual learning environment in support of the mathematics, which helped to the mutual learning and to the students' motivation. The design of the research was not experimental. The sample consisted of the students of the ninth year of general basic education of the Educational Unit "Amelia Gallegos Díaz". For the data collection, a survey aimed for teachers, and students in order to know the level of satisfaction of the Virtual Learning Environment developed in the LMS Chamilo and it was obtained a positive result of 88.4%. The EVA was developed in the LMS Chamilo, free access tool that allowed evidence that is an interesting and attractive when we use the interface tool.